2016
DOI: 10.1055/s-0036-1579665
|View full text |Cite
|
Sign up to set email alerts
|

Combined Medial Patellofemoral Ligament Reconstruction and Tibial Tubercle Transfer Results at a Follow-Up of 2 years

Abstract: There is limited data on the effectiveness of combined medial patellofemoral ligament (MPFL) reconstruction and tibial tubercle transfer (TTT) in patients with patella instability. The aim of our study was to analyze the functional outcome in patients treated with MPFL reconstruction and TTT. Between July 2008 and April 2013, 18 patients (21 knees) underwent combined MPFL reconstruction and TTT; 15 patients (16 knees) with a mean age of 24 years (16-41) had a mean follow-up of 30 months (26-55). There was sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…19.1% of knees were classified to have a normal trochlea, type A TD was observed in 27.9 %, type B was observed in 29.4 %, type C was observed in 19.1%, and 4.4% had TD type D. Another three knees could not be classified (4.4 %). Mean CDI was 1.4 [ 1 , 2 ]. In 77.5 % of the knees, patella alta (CDI > 1.2) was observed (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…19.1% of knees were classified to have a normal trochlea, type A TD was observed in 27.9 %, type B was observed in 29.4 %, type C was observed in 19.1%, and 4.4% had TD type D. Another three knees could not be classified (4.4 %). Mean CDI was 1.4 [ 1 , 2 ]. In 77.5 % of the knees, patella alta (CDI > 1.2) was observed (Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Lateral patella dislocation occurs in 5.8 to 77.8 of 100,000 patients per year [ 1 , 2 ]. Without surgical treatment redislocation occurs in up to 40–70% [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the combination of MPFL reconstruction and ATT transposition in patients with trochlear dysplasia produce good clinical results and low degrees of re-dislocation, in agreement with the literature [ 18 ]. In our study, the pre-operative TT-TG distance did not affect the clinical results at the final and intermediate follow-ups, considering the disagreement in the literature regarding the measure being seen as pathological [ 1 ]. According to Matsushita et al [ 23 ] no statistically significant difference in clinical scores was obtained between patients with a TT-TG distance > 20 mm and those with a TT-TG distance < 20 mm who underwent surgery for patellar instability.…”
Section: Discussionmentioning
confidence: 79%
“…Trochlear dysplasia is one of the most important predisposing factors, having been confirmed as a radiological finding in 85% of patients with a history of recurrent lateral patella dislocations [ 2 ]. Other important bony abnormalities that contribute to patellar instability are high tibial tubercle to trochlear groove (TT-TG) distance, patellar height, pathological patellar tilt and sulcus angle [ 1 , 8 ]. Moreover, medial patellofemoral ligament (MPFL) rupture, which contributes from 50 to 60% of the total medial restraining force against lateral patellar dislocation at 0° to 30° degrees of knee flexion [ 7 ], represents the main risk factor among all soft-tissue abnormalities that cause patellar instability.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review by Vivekanantha et al [28] reported a pooled rate (four relevant studies) of return to sport among patients undergoing MPFLR with TTO to be 92%, compared to 82% among iMPFLRs. On the other hand, numerous case series have reported return to sport rates following TTO and MPFLR with TTO, ranging from 57% to 100% [14,[29][30][31][32][33]. In a systematic review by Platt et al [17], they concluded that additional osteotomy does not affect the rate or time to return to sport.…”
Section: Discussionmentioning
confidence: 99%